January 2024 Placement ADS (The Accounting Review, 2024)
UNIVERSITY OF MINNESOTA, Carlson School of Management, Department of Accounting is seeking applications from candidates who are interested in a position as an Assistant Professor.All applicants must possess or be near completion of a